The Students’ Ability in Arranging Jumbled Words into Sentences at State Vocational High School - Wati, Ira; Yusrida, Yusrida (State Islamic University of Sultan Syarif Kasim Riau, 2024)
This research comprises one variable, how is students’ ability in arranging jumbled words into simple present sentences at State Vocational High School 1 Pendalian IV Koto. The research aimed to knowing the students’ ability in arranging jumbled words into simple present sentences especially tenth grade of State Vocational High School 1 Pendalian IV Koto. The design of this research is descriptive quantitative. The research used quantitative data, where the students were assessed by their score. The total population is 90 students consist of 4 classes that are TKJ 1: 21 students, TKJ 2: 21 students, AKT 1: 23 students, and AKT 2: 25 students. This research used cluster sampling and get of class AKT 1: 23 students. The instrument of the research was test (arranging jumbled words) consist 20 questions. In collecting the data of the research, the researcher used written test by duration 45 minutes. Based on the result of the research, there were 1 student on Very Good category (4.34%), 3 students on Good category (13.04%), 7 students on Enough category (30.43%), and 12 students on Less category (52.17%). Based on the average value, the students’ ability in arranging jumbled words into simple present sentences in the tenth grade of Vocational High School 1 Pendalian IV Koto is included in the less category.